The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1590/s1516-89132002000600011
|View full text |Cite
|
Sign up to set email alerts
|

Bionomic aspects of Pattonella intermutans (Thomson, 1869) (Diptera, Sarcophagidae) under laboratory conditions

Abstract: Life and fertility tables of Pattonella intermutans (Thomson, 1869) were studied in the laboratory conditions. The flies colonies were maintained at 20-28°C, 80±10% RH and observed daily. Life expectancy was 2.34 weeks for males and 2.33 weeks for females. The survivorship curves presented a type II tendency for females and type III for males. The periods of pre-larviposition and larviposition were of 2.5 and 9.5 weeks, respectively. Using data of the life table of fertility, the following values were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 5 publications
1
4
0
4
Order By: Relevance
“…This result is similar to the behavior found in Campinas, SI=-94.30 (Linhares 1981) and Rio de Janeiro, SI=-60.1 (D'Almeida 1984); but it significantly differs from the results of Belo Horizonte, SI=4.2 (Dias et al 1984) where P. intermutans showed independence from inhabited areas and was found in the three areas, with a lower proportion in the urban area. This species showed a necrophagous behavior, also exhibited in other studies (Linhares 1981, D'Almeida 1984, D'Almeida & Lima 1994, for this reason several taxonomists have remarked its importance in forensic entomology (Carvalho et al 2000, Oliveira et al 2002, Barros et al 2008.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This result is similar to the behavior found in Campinas, SI=-94.30 (Linhares 1981) and Rio de Janeiro, SI=-60.1 (D'Almeida 1984); but it significantly differs from the results of Belo Horizonte, SI=4.2 (Dias et al 1984) where P. intermutans showed independence from inhabited areas and was found in the three areas, with a lower proportion in the urban area. This species showed a necrophagous behavior, also exhibited in other studies (Linhares 1981, D'Almeida 1984, D'Almeida & Lima 1994, for this reason several taxonomists have remarked its importance in forensic entomology (Carvalho et al 2000, Oliveira et al 2002, Barros et al 2008.…”
Section: Discussionsupporting
confidence: 76%
“…With this study we have reported seven new records for Colombia, many of them previously recorded for other countries in the Neotropical and Neartic regions (Lopes 1975, Lopes & Tibana 1991, Pape 1996, Oliveira et al 2002, Pape et al 2004. These results allow us to resume a total of 85 species of this family for Colombia.…”
Section: Discussionmentioning
confidence: 71%
“…Leal et al (1982) reported the same results for Chrysomya putoria (Wiedemann, 1818), on which they tested artificial diets and used mouse carcass to feed the control group. Bovine meat has been used by many authors as the preferential diet to rear muscoids dipteran (Oliveira et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Para a manutenção das colônias e obtenção das neolarvas de P. intermutans utilizou-se a metodologia descrita por Oliveira et al (2002). Em cada repetição (4) foram inoculadas 25 neolarvas em 25 g de dieta, perfazendo o total de 200 larvas/ dieta.…”
Section: Methodsunclassified